Discovering Subsolar Metallicity Brown Dwarf Candidates in the Small Magellanic Cloud - Peter Zeidler; Elena Sabbi; Antonella Nota; Elena Manjavacas; Olivia C. Jones; Camilla Pacifici (The Astrophysical Journal)
We present the discovery of the first rich population of brown dwarf candidates (cBD) at subsolar metallicity, observed by JWST outside the Milky Way (MW) in the young SMC star cluster NGC 602. Located in the Small Magellanic Cloud (SMC) “wing,” in a very low-density environment (1.3 cm ^−3 ) and at subsolar metallicity, NGC 602 is very young, with an age of 2–3 Myr. The low stellar density in this star cluster together with JWST NIRCam images in eight filters allowed us to individually resolve and derive accurate photometric measurements for 64 candidate BDs with masses ranging from 0.05 to 0.08 M _⊙ or 50 to 84 M _Jup , according to brown dwarf (BD) evolutionary models. This is the first detection of a young BD population outside the MW. Their spatial distribution indicates that they appear colocated with the pre-main-sequence stars. Although further detailed work is required to quantitatively derive the initial mass function and confirm the true nature of the cBD, this discovery is particularly relevant in the effort to refine our understanding of the subsolar mass function at very low metallicities and young ages.